Banking sector (under?) development in Central and Eastern Europe - Jürgen von Hagen; Valeriya Dinger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2005)
By introducing a new measure of the banking systems' size, the paper challenges the existing consensus on severe underdevelopment of the CEE banking sectors. We argue that the existing studies on the size of CEE banking systems exaggerate the real degree of underdevelopment because common measures of the size of the banking system produce downward biased results when applied to transition economies. We compare various measures of the size of the CEE banking sectors with those of several 'old' European Union (EU) member countries which are used as benchmarks. The comparison indicates that indeed the banking sectors in the CEE countries lag behind the most developed financial systems in the EU, but are very close to the levels in the financially less developed EU countries.
Keywords: G21; P34; 330; financial intermediation; transition economies; banking sector's size; Bankensystem; Finanzsektor; Entwicklung; Finanzintermediär; Osteuropa